Magnetic effects of thaumatin crystals; observation of crystal growth by magneto-Archimedes levitation and magnetic orientation - Syou Maki; Masao Fujiwara; Yoshihisa Fujiwara; Makoto Nakabayashi; Shotaro Morimoto; Seiichi Tanaka; Seiji Fujiwara; Masayuki Hagiwara; Kohji Inaka (PLoS ONE, 2025)
We examined the magnetic effect of thaumatin crystals, which are a well known model of protein crystals but which have hardly been studied for that effect. We succeeded in crystallizing thaumatin by magnetic levitation based on the magneto-Archimedes effect by the addition of the paramagnetic substance gadolinium chloride. We also carried out a chronological observation of the levitation process in a superconducting magnet, and visualized the magnetic orientation of the crystals by applying a magnetic field along the horizontal direction. In another major result, we carried out a diffraction experiment and performed a structural analysis of the crystals. We noticed from the results that no electron density from the gadolinium ion could be observed in the crystals. This suggests the possibility that the paramagnetic substance of the aqueous precipitant solution helps only to promote the crystals’ levitation, and has little effect on thaumatin crystallization.